حقوق الإنسان في عصر التحولات الدولية الكبرى - كربوسه, عمراني; دراجي, هشام (Revue jurisprudence, 2019)
This article begins with an attempt to identify the formal and objective differences between the reality of human rights practice in the light of the strategic changes that took place in the world after the events of September 11, 2001 in the United States. The latter changed its discourse on human rights issues from a democratic discourse based on humanism to speech the most recent contradiction depends on security in the face of the threat of terrorism and extremism. This change, whose repercussions have caused many cracks in the structure of the international human rights system, which in turn has known many serious violations. Human Rights - Transformations - Humanity – Security